Combining froth flotation and reflux classification to mitigate ARD generating potential of the Waterberg and Witbank coal ultrafines via sulfide removal - Iroala, Onyinye Judith (Centre for Bioprocess Engineering Research, 2015)
In South Africa, over 10 million tons of ultrafine coal wastes are discarded every year, typically in the form of ultrafine slurries. These fines have a high calorific value, and contain sulfur minerals, particularly pyrite. The high calorific value of these discards leads to a waste of energy that could be harnessed and used, while the high sulfur content contributes to adverse environmental effects such as acid rock drainage (ARD). The University of Cape Town (UCT) has developed a two-stage flotation process, which involves coal flotation in the first stage and pyrite flotation of the tailings in the second stage, for mitigating the ARD potential of ultrafine wastes. Research has shown that this two stage froth flotation process was sufficient to render the tailings non-acid forming. At the same time, North West University (NWU) has been carrying out research on coal fines using the recently invented reflux classifier. The reflux classifier is claimed to be capable of separating particles down to 38 ìm in size; however, no work has been done using the reflux classifier to separate pyrite from coal. This dissertation investigates the effectiveness of combining flotation and reflux classification for removing sulfide minerals from two South African coal ultrafines, whilst recovering valuable coal, and compares the results to those obtained using the UCT two-stage flotation process. As no previous work has been done using reflux classification to remove sulfide minerals from coal, this is the first time that the reflux classifier will be investigated for this purpose. Two process routes were investigated: (i) froth flotation followed by reflux classification of the tailings (process route 1), and (ii) reflux classification followed by froth flotation of the overflow (process route 2). Coal flotation, sulfide flotation and reflux classification were conducted on samples of Waterberg and Witbank coals, using a 3 L Leeds-type flotation cell and a 10 L batch reflux classifier constructed at NWU. Acid base accounting (ABA) and net acid generating (NAG) static characterization tests were performed on the products and feeds from all three process routes.